198k views
4 votes
Multiply.

(3x+4)(2x−1)

Express the answer in standard form.

Enter your answer in the box.

User Rickroyce
by
5.1k points

2 Answers

3 votes

(3x + 4)(2x - 1) distributive

= (3x)(2x) + (3x)(-1) + (4)(2x) + (4)(-1) = 6x² - 3x + 8x - 4

combine like terms

= 6x² + 5x - 4

Answer: (3x + 4)(2x - 1) = 6x² + 5x - 4

User Ben In CA
by
5.1k points
7 votes

(3x+4)(2x−1)

FOIL (first outer inner last)

3x*2x + 3x*(-1) + 4*2x+4*(-1)

6x^2 -3x+8x -4

6x^2 +5x-4

User Craftsman
by
5.4k points